Novel features of centriole polarity and cartwheel stacking revealed by cryo‐tomography. (20th September 2020) - Nazarov, Sergey; Bezler, Alexandra; Hatzopoulos, Georgios N; Nemčíková Villímová, Veronika; Demurtas, Davide; Le Guennec, Maeva; Guichard, Paul; Gönczy, Pierre
Abstract: Centrioles are polarized microtubule‐based organelles that seed the formation of cilia, and which assemble from a cartwheel containing stacked ring oligomers of SAS‐6 proteins. A cryo‐tomography map of centrioles from the termite flagellate Trichonympha spp. was obtained previously, but higher resolution analysis is likely to reveal novel features. Using sub‐tomogram averaging (STA) in T.  spp. and Trichonympha agilis, we delineate the architecture of centriolar microtubules, pinhead, and A‐C linker. Moreover, we report ~25 Å resolution maps of the central cartwheel, revealing notably polarized cartwheel inner densities (CID). Furthermore, STA of centrioles from the distant flagellate Teranympha mirabilis uncovers similar cartwheel architecture and a distinct filamentous CID. Fitting the CrSAS‐6 crystal structure into the flagellate maps and analyzing cartwheels generated in vitro indicate that SAS‐6 rings can directly stack onto one another in two alternating configurations: with a slight rotational offset and in register. Overall, improved STA maps in three flagellates enabled us to unravel novel architectural features, including of centriole polarity and cartwheel stacking, thus setting the stage for an accelerated elucidation of underlying assembly mechanisms. Synopsis: Centrioles are microtubule‐based organelles that are essential for cilia assembly across eukaryotes. Cryo‐electron tomography of termite flagellates delineates the architecture of the centriole proximal region, which contains a SAS‐6‐based cartwheel, as well as peripheral pinhead, A‐C linker, and microtubule triplets. Centriolar cartwheel inner densities (CID) are polarized in Trichonympha centrioles. A continuous filamentous CID (fCID) is present in Teranympha centrioles. SAS‐6 rings can directly stack in vitro . SAS‐6 rings stack in two ways in vivo : either with an offset, or in register. Abstract : Ultrastructural studies of centrioles from termite flagellates delineate the architecture of the centriole proximal region, including new insights into stacking of cartwheel‐forming SAS‐6 rings.